The handbook of magazine studies - Sternadori, Miglena; Holmes, Tim, 1953- (Hoboken, N. Jersey John Wiley and Sons, 2020)
"The past two decades have witnessed increased scholarly interest in new media and social media, which encompass some of the aspects of the magazine format--especially in creating and maintaining interpretive communities. Yet, despite the hope that the impact of the web and digital technologies would inspire new trajectories in magazine research, few magazine studies are being published in academic journals or presented at academic conferences. The handbook will address the need for more theoretically grounded magazine research that is also socially and historically contextualized. It will begin to formulate the field of magazine studies, which has been and will be of interest to scholars from the fields of journalism, communication, critical and cultural studies, literary studies, sociology, history, business, and education"--
Includes bibliographical references and index.
Keywords: Periodicals -- Publishing; Periodicals -- Social aspects; Periodicals -- Publishing -- Economic aspects; Magazines; Journalism